Radiocarbon dating of Vučedol culture complex - Durman, Aleksandar (Array, 1989)
Radiocarbon dates of the Vučedol culture range from its earliest beginnings at Vucedol and Pivnica to its late phase at Vinkovci, Eastern Slavonia, Hrustovača, northwest Bosnia, Parte, Slovenia and Rudine, northwest Croatia. Recent 14^C analyses are discussed and compared to corresponding dates outside the scope of the Vučedol culture. Findings provide evidence for the expansion of the late Vučedol culture both in time and space.